ChatGPT Jadi ‘Ustadz’? Tantangan dan Peluang AI dalam Riset Islam di Era Digital - Riska Ramadhani; Tri Suryani; Ahmad Naufal; Abdul Fadhil (Yayasan Al-Afif, 2025)
This study analyzes the role of ChatGPT as AI in Islamic research and the opportunities and challenges emerging in the digital era. Using a library research method, it reviews literature on AI, Islamic scholarly ethics, and digital technology. The findings show that ChatGPT supports faster literature access, concept mapping, and initial analysis of research themes. It also assist in formulating research problems and building theoretical framework. However challenges remain, including information accuracy, algorithmic bias, limited contextual understanding, and the absence of religious authority. Therefore, ChatGPT must be used critically and verified through primary sources. The study concludes that ChatGPT is a complementary tool and cannot replace scholars or Islamic scientific methodology.